(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This article examines the disparities in educational opportunities between rural and urban children from historical, social, and pedagogical perspectives. It highlights the close relationship between the development of education systems, urbanization processes, production relations, and cultural environments. Drawing on international and national studies, the paper identifies the key factors contributing to territorial educational inequality and emphasizes the critical role of primary education in shaping learning motivation and cognitive skills. The study underscores the importance of improving the quality of rural education to promote social equity.